Pendekatan Desain Pembelajaran Humanistik dalam Meningkatkan Motivasi Belajar - Zul Hafriadi Rahmat; Yogi Tri Gustian; Gusmaneli Gusmaneli (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The humanistic instructional design approach offers an effective strategy to enhance students' learning motivation by placing them at the center of the learning process. This study aims to analyze the implementation of this approach in Islamic Religious Education (PAI) and its impact on students' learning motivation. A descriptive qualitative method with a field study approach was employed, combining observations, interviews, and documentation analysis. The findings reveal that the humanistic approach fosters students' enthusiasm, strengthens teacher-student relationships, and supports the development of independence and learning responsibility. In PAI learning, this approach connects subject matter to real-life contexts, enabling students to understand and apply religious values in their daily lives. Despite challenges in its implementation, the approach proves to be relevant and effective in creating meaningful, holistic, and sustainable learning experiences.